Reaction Kinetics of Waste Cooking Oil Hydrocracking into Biofuel Using Ni-Impregnated Mesoporous Silica Catalyst - Salamah, Siti; Trisunaryanti, Wega; Kartini, Indriyana; Purwono, Suryo (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
The growing demand for energy and the scarcity of fossil fuel resources have driven research into alternative fuels, one of which being the conversion of waste cooking oil into biofuel through hydrocracking. This study investigates the reaction kinetics of waste cooking oil hydrocracking using a Ni-impregnated mesoporous silica catalyst. The process was conducted at 450 °C with a hydrogen gas flow to produce products such as green naphtha, green gasoline, and green diesel. The proposed reaction kinetics model was the pseudo-first order, solved using differential and integral methods. The results showed that the first-order reaction provided a more representative outcome, with a reaction rate constant (k’) of 0.276 h⁻¹ at 450 °C. Additionally, the Arrhenius kinetic model revealed an activation energy of 37.8748 kJ/mol for this process. Thus, this study demonstrates a significant potential of using mesoporous silica catalysts in waste cooking oil hydrocracking to produce environmentally friendly and economically viable biofuels. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).